Moonlighting glycolytic protein glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH): an evolutionarily conserved plasminogen receptor on mammalian cells. Issue 6 (15th March 2017) - Chauhan, Anoop Singh; Kumar, Manoj; Chaudhary, Surbhi; Patidar, Anil; Dhiman, Asmita; Sheokand, Navdeep; Malhotra, Himanshu; Iyengar Raje, Chaaya; Raje, Manoj
ABSTRACT: Prokaryotic pathogens establish infection in mammals by capturing the proteolytic enzyme plasminogen (Plg) onto their surface to digest host extracellular matrix (ECM). One of the bacterial surface Plg receptors is the multifunctional glycolytic enzyme glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH). In a defensive response, the host mounts an inflammatory response, which involves infiltration of leukocytes to sites of inflammation. This requires macrophage exit from the blood and migration across basement membranes, a phenomenon dependent on proteolytic remodeling of the ECM utilizing Plg. The ability of Plg to facilitate inflammatory cell recruitment critically depends on receptors on the surface of phagocyte cells. Utilizing a combination of biochemical, cellular, knockdown, and in vivo approaches, we demonstrated that upon inflammation, macrophages recruit GAPDH onto their surface to carry out the same task of capturing Plg to digest ECM to aid rapid phagocyte migration and combat the invading pathogens. We propose that GAPDH is an ancient, evolutionarily conserved receptor that plays a key role in the Plg‐dependent regulation of macrophage recruitment in the inflammatory response to microbial aggression, thus pitting prokaryotic GAPDH against mammalian GAPDH, with both involved in a conserved role of Plg activation on the surface of their respective cells, to conflicting ends.—Chauhan, A. S., Kumar, M., Chaudhary, S., Patidar, A., Dhiman, A., Sheokand, N., Malhotra, H., Raje, C. I., Raje, M. Moonlighting glycolytic protein glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH): an evolutionarily conserved plasminogen receptor on mammalian cells. FASEB J. 31, 2638–2648 (2017). www.fasebj.org